2002
DOI: 10.1021/jf011416e
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Marker for ALS-Inhibitor Herbicides:  2-Aminobutyric Acid Proportional in Sub-Lethal Applications

Abstract: A chemical profiling technique for sub-lethal acetolactate synthase (ALS)-inhibitor herbicides (e.g., sulfonylureas, imidazolines, triazolopyrimidine sulfonanilides, and pyrimidyloxy salicylic) was developed using 2-aminobutyric acid, and was found to be directly proportional to application rates in field studies on two varieties of potato plants. An uncomplicated, benign-by-design analytical method for the determination of 2-aminobutyric acid in plant tissue was developed. The method is simple, fast, and auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…For tests with L. gibba , extraction, purification and quantification procedures exist for polar and non-polar compounds (plastoquinone, ubiquinone, β-sitosterol and stigmasterol) (Brain et al 2006) , and are based on protocols for algae (Schwender et al 1996) and seaweeds (Sánchez-Machado et al 2004) . Extraction and quantification methods also exist for metabolites that accumulate in the presence of ALS-(acetolactate synthase) inhibiting herbicides (2-aminobutyric acid) (Loper et al 2002) and glyphosate (shikimic acid), respectively (Harring et al 1998 ;Lydon and Duke 1988) . Published methods for the extraction and purification of enzymes (ALS and 5-enolpyruvylshikimic acid-3phosphate (EPSP)-synthase) are also available (Ray 1984 ;Amrhein et al 1983) .…”
Section: Quantificationmentioning
confidence: 99%
See 3 more Smart Citations
“…For tests with L. gibba , extraction, purification and quantification procedures exist for polar and non-polar compounds (plastoquinone, ubiquinone, β-sitosterol and stigmasterol) (Brain et al 2006) , and are based on protocols for algae (Schwender et al 1996) and seaweeds (Sánchez-Machado et al 2004) . Extraction and quantification methods also exist for metabolites that accumulate in the presence of ALS-(acetolactate synthase) inhibiting herbicides (2-aminobutyric acid) (Loper et al 2002) and glyphosate (shikimic acid), respectively (Harring et al 1998 ;Lydon and Duke 1988) . Published methods for the extraction and purification of enzymes (ALS and 5-enolpyruvylshikimic acid-3phosphate (EPSP)-synthase) are also available (Ray 1984 ;Amrhein et al 1983) .…”
Section: Quantificationmentioning
confidence: 99%
“…Although not empirically compared to a morphological parameter such as growth, Loper et al (2002) demonstrated the utility of 2-aminobutyric acid (2-aba) as an exclusive biomarker for ALS-inhibiting herbicides. Present at ppm (parts per million) concentrations in plant tissue, 2-aba is a precursor for branched chain amino acid synthesis utilized by ALS, and is therefore a useful marker.…”
Section: Applications To Evaluate Xenobiotic Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…The negative consequences of such ecological contamination have increased the demand for monitoring systems to ensure water quality. The systemic herbicide 2,4-dichlorophenoxyacetic acid (2,4-D) (Figure 1) is widely used in a variety of agricultural and non-agricultural applications, and is typically monitored in environmental samples using HPLC methods, which require clean-up, although, a number of potential field analytical methods have been reported (Garimella et al 2000;Loper et al 2002). Currently, 2,4-D contamination of water is ruled out by HPLC analysis using standard methods (Anastassiades and Schwack 1998;Wells et al 2002).…”
Section: Introductionmentioning
confidence: 99%